Are patients with mild to moderate renal impairment on metformin or other oral anti-hyperglycaemic agents at increased risk of contrast-induced nephropathy and metabolic acidosis after radiocontrast exposure?. Issue 8 (August 2019) - Jung, J.; Cho, Y.Y.; Jung, J.H.; Kim, K.Y.; Kim, H.S.; Baek, J.-h.; Hahm, J.R.; Cho, H.S.; Kim, S.K.
Abstract : AIM: To investigate whether the use of metformin during computed tomography (CT) with radiocontrast agents increases the risk of contrast-induced nephropathy (CIN) and metabolic acidosis after CT in type 2 diabetes patients with mild to moderate renal failure. MATERIALS AND METHODS: Patient records from January 2015 to December 2017 were reviewed retrospectively. A total of 374 patients were included in the final analysis. Of them, 157 patients received metformin, and 217 patients were taking other oral hypoglycaemic agents (OHAs) during radiocontrast administration. RESULTS: No significant difference in CIN incidence was observed between the metformin use group and the other OHAs group ( p= 0.085). Metabolic acidosis after CT was seen in 91 (58%) patients who used metformin and 141 (65%) patients who were taking other OHAs. There was no relationship between metabolic acidosis after CT and the use of metformin ( p= 0.195). Metabolic acidosis after radiocontrast agent exposure was associated with malignant disease, low serum albumin level, and low serum total CO2 level at baseline. CONCLUSION: These data show that other factors, but not metformin use, are associated with metabolic acidosis after radiocontrast agent exposure in patients with reduced renal function. These data support current recommendations that there is no need to discontinue metformin before CT using radiocontrast agents in patients with mild to moderate renal failure. Highlights: Metformin use was not related with contrast-induced nephropathy in type 2 diabetic patients. Metformin use was not related to metabolic acidosis after radiocontrast agent use in type 2 diabetic patients. Low serum albumin level, and low serum total CO2 level were associated with metabolic acidosis after radiocontrast agent use.